Study on the selection criteria for choosing domestic package tours in Malaysia - Abang Josmani, Dayang Sandrawati (2007)
This study was designed to identify important selection factors for domestic package tours in Malaysia. A total of 21 selection criteria were identified in this study, which is applied from a similar but outbound research in Hong Kong done by Chak-Keung Simon Wong and Wai Yan, 2003. From the study, it shows that price is the most important criteria for Malaysian in choosing their domestic package tour, followed by the safety of the tour, service quality offered by the travel agency, escorts, tour guides quality and experience, comfortable transportation and meals provided. All of these criteria were viewed as important with mean score greater than 4. This conclude that Malaysian people are very particular about the price of the tour package when they planning to travel. Malaysian also would consider on the service quality provided the travel agency which will of course goes to the experienced tour guide and tour leader or manager during the tour. As we know, Malaysian is very keen in having a comfort journey which will reflect to the comfortable transportation provided and also meals during the tour especially muslim which will prefer halal food. Recommendations for travel agencies, included price and safety of tour, training for escorts and tour-guides, itinerary and customer care services, will, it is argued, enhance the attractiveness of package tours and their competitiveness.